Optimization of comparative genomic hybridization using fluorochrome conjugated to Dctp and Dutp nucleotides - Elrifai, Wa`el (1997)
Fil: Elrifai, Wa`el. Department of Medical Genetics. Haartman Institute. University of Helsinki. Helsinki; Finland